2020
DOI: 10.1002/cncr.33310
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported causes of distress predict disparities in time to evaluation and time to treatment after breast cancer diagnosis

Abstract: Background We examined whether the National Comprehensive Cancer Network distress thermometer (DT), a patient‐reported outcome measure, could be used to identify levels and causes of distress associated with racial/ethnic disparities in time to care among patients with breast cancer. Methods We identified women aged ≥18 years with stage 0‐IV breast cancer who were diagnosed in a single health system between January 2014 and July 2016. The baseline visit was defined as the first postdiagnosis, pretreatment clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…However, our findings demonstrate that expanding access to care is not a panacea, and mitigating insurance as a barrier is not enough to achieve equity. Previous work has identified numerous other potentially modifiable barriers to timely treatment, including a lack of support with childcare, household responsibilities, job‐related demands, and care coordination 26‐28 . Thus, the racial/ethnic minority women served by NC BCCCP may still disproportionately face other challenges that keep them from attaining equitable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings demonstrate that expanding access to care is not a panacea, and mitigating insurance as a barrier is not enough to achieve equity. Previous work has identified numerous other potentially modifiable barriers to timely treatment, including a lack of support with childcare, household responsibilities, job‐related demands, and care coordination 26‐28 . Thus, the racial/ethnic minority women served by NC BCCCP may still disproportionately face other challenges that keep them from attaining equitable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that White women reported greater distress than Black women is consistent with previous epidemiologic surveys that Black women report lower levels of distress compared with White women during cancer treatment and in later survivorship. 51 , 52 , 53 Prior research identified several potential protective factors that may be associated with this difference (eg, resilience, social support, and religious beliefs). 51 , 54 Moreover, Black women may use different coping strategies (eg, suppressing emotions and wishful thinking) that may be associated with lower reporting of distress, whereas White women may be more comfortable expressing emotions.…”
Section: Discussionmentioning
confidence: 99%
“… 51 , 52 , 53 Prior research identified several potential protective factors that may be associated with this difference (eg, resilience, social support, and religious beliefs). 51 , 54 Moreover, Black women may use different coping strategies (eg, suppressing emotions and wishful thinking) that may be associated with lower reporting of distress, whereas White women may be more comfortable expressing emotions. 55 Accordingly, our decomposition results suggest that, if Black women had the same characteristics as White women, they would have reported even lower (ie, better) distress composite scores, widening the gap between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not suggest that PROs can solve the lack of access to medical care for various communities, they may help in identifying barriers or challenges to those who have not received care. 17 This becomes particularly powerful when PROMS are co-administered with social determinants of health questionnaires, allowing researchers and clinicians to better quantify the differential impact of surgery on the lives of patients with more or less social stressors. This not only facilitates quality improvement but allows surgeons and researchers to tailor interventions to improve equity in care and provide better patient counseling.…”
Section: Implementation Of Pro Datamentioning
confidence: 99%